Theoretical Study on Frontier Orbitals of Dehydrogenated Tetrahydrocurcumin in Gas Phase - Lusia S. P. Boli, .- (IOP Publishing, 2019)
In this present work, we calculated two frontier orbital energies - singly occupied molecular orbital (SOMO) and lowest unoccupied molecular orbital (LUMO) - of dehydrogenated tetrahydrocurumin (THC) using density-functional theory (DFT) in gas phase. We used the energy difference of SOMO and LUMO to assess the stability of dehydrogenated THC after performing a hydrogen atom transfer toward reactive oxygen species (ROS). We began by optimizing dehydrogenated THC at six hydrogen abstraction sites. Two hydrogen abstraction sites are at O-H groups and four hydrogen abstraction sites are at C-H groups. Then, we compared the value of SOMO and LUMO energy difference in each site. Our calculations showed that dehydrogenated THC at O-H groups are more stable than dehydrogenated THC at C-H groups.